Diastolic wall strain is associated with incident heart failure in African Americans: Insights from the atherosclerosis risk in communities study. Issue 5 (May 2018) - Kamimura, Daisuke; Suzuki, Takeki; Hall, Michael E.; Wang, Wanmei; Winniford, Michael D.; Shah, Amil M.; Rodriguez, Carlos J.; Butler, Kenneth R.; Mosley, Thomas H.
Highlights: The association between left ventricular (LV) myocardial stiffness and incident heart failure is proposed. Diastolic wall strain assessed by echocardiography was used as a LV stiffness indicator. Increased LV myocardial stiffness was associated with incident heart failure. Abstract: Background: Increased left ventricular (LV) myocardial stiffness may be associated with impaired LV hemodynamics and incident heart failure (HF). However, an indicator that estimates LV myocardial stiffness easily and non-invasively is lacking. The purpose of this study was to determine whether diastolic wall strain (DWS), an echocardiographic estimator of LV myocardial stiffness, is associated with incident HF in a middle-aged community-based cohort of African Americans. Methods and results: We investigated associations between DWS and incident HF among 1528 African Americans (mean age 58.5 years, 66% women) with preserved LV ejection fraction (EF ≥50%) and without a history of cardiovascular disease in the Atherosclerosis Risk in Communities Study. Participants with the smallest DWS quintile (more LV myocardial stiffness) had a higher LV mass index, higher relative wall thickness, and lower arterial compliance than those in the larger four DWS quintiles ( p  < 0.01 for all). Over a mean follow-up of 15.6 years, there were 251 incident HF events (incidence rate: 10.9 per 1000 person-years). After adjustment for traditional risk factors and incident coronary artery disease, both continuous and categorical DWS were independently associated with incident HF (HR 1.21, 95%CI 1.04–1.41 for 0.1 decrease in continuous DWS, p  = 0.014, HR 1.40, 95%CI 1.05–1.87 for the smallest DWS quintile vs other combined quintiles, p  = 0.022). Conclusions: DWS was independently associated with an increased risk of incident HF in a community-based cohort of African Americans. DWS could be used as a qualitative estimator of LV myocardial stiffness.